Active Learning through Role Play: Its Impact on Critical Thinking and Conceptual Understanding in Madrasah Tsanawiyah: Pembelajaran Aktif melalui Bermain Peran: Dampaknya terhadap Berpikir Kritis dan Pemahaman Konseptual di Madrasah Tsanawiyah - Fitrah , Ramadhani Fauzi; Shendy, andrie Wijaya; Jhoni, Susanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the effectiveness of role-playing as an active learning strategy in enhancing students’ critical thinking and conceptual understanding in economics education at Madrasah Tsanawiyah. Addressing the paucity of evidence on interactive pedagogies in faith-based secondary schools, the research contrasts role-play with conventional lecture-based approaches that often fail to foster higher-order reasoning. A quasi-experimental design with a non-equivalent control group was employed, involving two intact classes (N = 70) assigned to either a role-play intervention or traditional instruction. Data were collected using validated instruments assessing four dimensions of critical thinking and standardized tests of conceptual understanding. ANCOVA results demonstrated significant improvements in the experimental group, with adjusted mean differences of 5.27 points for critical thinking and 10.50 points for conceptual understanding (p < .001), supported by large effect sizes. These outcomes suggest that role-playing creates experiential learning contexts that stimulate analytical reasoning, perspective-taking, and reflective judgment, thereby promoting deeper and more transferable learning. The findings not only reinforce existing evidence on the value of active learning but also underscore the unique potential of role-playing to cultivate 21st-century competencies in religious educational contexts. The study concludes that role-playing represents a robust pedagogical approach for advancing cognitive development in secondary economics, while further research is recommended to explore its long-term and cross-disciplinary applicability